Application of Conductivity Combined with Various Other Instrumental Analyses in the Detection of the Freshness and Yolk-to-White Ratio of Liquid Egg - DOU Wenhao, WANG Hailing, HUANG Zilong, YANG Fuming, CHI Yuan, CHI Yujie (Shipin Kexue, 2024)
This study established a rapid and efficient technique to detect the freshness and yolk-to-white ratio of liquid egg based on conductivity combined with salinity, total dissolved solids (TDS), pH, and color parameters. The results showed that during the storage period of 0-45 days at 4 ℃, the conductivity, salinity, and TDS of egg yolk and egg white gradually increased. The color difference index and egg yolk pH of both decreased significantly, while the pH of egg white gradually increased. It was found that the accuracy of conductivity in detecting the freshness of egg yolk and egg white was 91% and 89%, respectively, while that of conductivity combined with other indices was 94%. Based on this, the criteria to classify liquid egg into four grades of AA, A, B and C were established for the first time. AA liquid eggs were selected to detect yolk-to-white ratio using conductivity as the major index combined with salinity, TDS and pH. The experimental results proved that the conductivity, salinity, TDS and pH were all highly significantly and linearly correlated with the proportion of egg yolk in liquid egg; therefore, the proportion of egg yolk in unknown liquid egg samples could be detected based on the regression equations. The ExpAssoc model showed an average relative error of 8.87%, indicating high reliability. The results of this study provide a theoretical basis for the detection of the freshness and yolk-to-white ratio of blended liquid egg, and provide a reference for industrial producers of liquid egg.